Bilateral trade agreements and trade distortions in agricultural markets - Cornelius Hirsch; Harald Oberhofer (FIW - Research Centre International Economics, 2017)
Agricultural support levels are at a crossroad with reduced distortions in OECD countries and increasing support for agricultural producers in emerging economies over the last decades. This paper studies the determinants of distortions in the agricultural markets by putting a specific focus on the role of trade policy. Applying various different dynamic panel data estimators and explicitly accounting for potential endogeneity of trade policy agreements, we find that an increase in the number of bilateral free trade agreements exhibits significant short- and long-run distortion reducing effects. By contrast, WTO's Uruguay Agreement on Agriculture has not been able to systematically contribute to a reduction in agriculture trade distortions. From a policy point of view our findings thus point to a lack of effectiveness of multilateral trade negotiations.
Keywords: C23; C26; F13; F14; 330; agricultural distortions; WTO; bilateral trade agreements; panel data